OPPRESSION AGAINST WOMEN IN MICHAEL APTED'S ENOUGH MOVIE (2002) : A FEMINIST CRITICISM - PALUPI, LATIFUNISSA DYAH (2011)
The major problem in this study is how the oppression against women reflected in Michael Apted's Enough movie. The limitation is the violence against women of Slim Hiller as the major character. The objectives of the study are to analyze the structural elements and to analyze the oppression against women in Michael Apted's Enough movie by using Feminist Criticism. This research paper uses qualitative method which employs the collecting, describing, classifying, analyzing the data and drawing conclusion. The object of the study is Michael Apted's Enough movie published and distributed by Columbia Pictures. The primary data are the movie and movie subtitles. The secondary data sources including references and materials related to the study whether picking from books and/or internet. Based on its structural analysis, Michael Apted through this movie wants to delivers the message that the oppression against women shall be ended. Apted was success in building the plot and portraying the characters through the setdress, property and cinematograph that the elements are well related to one another forming a good unity. The conclusion of the study is Michael Apted's Enough movie depicts the oppression against women in America's society at the early of 21th century. It can be proved from the result of the analysis on the refusal to women's projection, the social existence of men and women which is not in nature, women's right as autonomous being, and materialist approach that supports the equality presented in this movie.